BROCCOLI PRODUCTION IN FUNCTION OF DOSES OF SULPHUR IN COVERAGE - CorrÃªa, Carla; Gouveia, Aline; Cardoso, Antonio (REVISTA DE AGRICULTURA, 2019)
The objective of this research was to evaluate the effect of sulfur doses in coverage production of AvengerÂ® hybrid broccoli. It was observed that the sulfur levels influenced the characteristics evaluated with linear effect for fresh mass, diameter, height, and inflorescence of fresh mass of leaves, with increase of 15.7 g; 0.29 cm; 0.46 cm, and 11.9 g per 10 kg of sulfur, respectively. There was no statistical difference in the number of sheets with an average of 25 leaves per plant.